Exploring Student’s Metacognitive Strategies Through Self-Reflection in Writing Assessments - Herry Augustinus Simarmata; Siti Drivoka Sulistyaningrum (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Writing is used as a tool for communication as well as learning, thinking, and organizing knowledge or ideas. Unfortunately, In Indonesian context, English writing represents a skill that is seen as exceptionally challenging for students. This study aimed to look into the metacognitive strategies employed by EFL students who were considered successful in writing assessments. The participants were seven students of English Education Master’s Program at Universitas Negeri Jakarta who completed writing assessments at the C1 level on the website. The text analysis method was used in this study. At the end of the lesson, students' self-reflection was examined to determine their metacognitive strategies in the cognitive, social, affective, and motivational domains. Each student's metacognitive strategy applications were quantified, and the metacognitive strategy content was classified and reported interpretively. According to the findings, students are more likely to use a variety of metacognitive strategies with the cognitive domain being the most frequently used domain when completing writing assessments. They were discovered to be goal-oriented, with a greater likelihood of focusing not only on a course-related objective but additionally on an objective to improve their language learning abilities. Furthermore, this study suggests that self-reflection can be used to investigate students’ learning strategies and to promote students' control over the writing skills learning process.